SDG 12 needs an oceanic interface: sand mining, saltwater intrusion (SWI) and coastal sustainability - Manan Sarupria; Naznin Nahar Sultana; Saleem H. Ali (Sustainable Earth Reviews)
Abstract The international development community has approached SDG 12 (Responsible Consumption and Production) through the lens of specific supply chains of consumer goods and services. For example, minerals from mines to markets; wood from forests to furniture; or food from farm to fridge, have been tracked in terms of their ecological profile in many of the SDG 12 targets. While such an approach can give us some idea of particular recycling or refurbishment opportunities, as well as waste-toenergy generation, it lacks a systems-oriented view on the interlinkages between socio-ecological systems of consumption and production. We argue that SDG 12 needs to be reimagined in terms of lateral impacts and connections in key sectors of resource extraction. Sand mining and saltwater intrusion (SWI) present an important example of how such a connection could be made between an anthropogenic activity in a coastal / marine environment and its ecological impact that could threaten food security. We present a review of research in this context that links these two seemingly disparate areas of academic inquiry. Focusing on the Mekong Delta we also consider how geospatial techniques could help to evaluate these connected impacts between sand mining and SWI and its consequential impacts on arable land and hence food availability and hunger. Considering a series of methodological challenges, we offer a way forward for measuring these impacts and charting a more integrative way forward for operationalizing SDG12 towards more sustainable environmental and social outcomes.